Depicting Precise Temperature and Duration of Vernalization and Inhibiting Early Bolting and Flowering of Angelica sinensis by Freezing Storage - Liu, Xiaoxia; Luo, Mimi; Li, Mengfei; Wei, Jianhe (Frontiers in Plant Science, 2022)
Angelica sinensis is a perennial rhizomatous herb that is widely used for the treatment of cardio-cerebrovascular diseases largely rely on metabolites alkylphthalides, polysaccharides and ferulic acid. This plant must experience low-temperature vernalization and long-day conditions for the occurrence of early bolting and flowering (EBF) that reduces yield and quality of fleshy root. In currently commercial planting, the EBF of ca. 40% mainly attributes to the completion of vernalization of seedlings during overwinter storage. While effects of storage temperatures [vernalization temperature (0 to 10°C) and freezing temperature (-2 to -12°C)] and seedling sizes on the EBF have been observed in previous studies, the precise vernalization temperature and duration for different seedlings, the effective freezing storage to avoid vernalization of seedlings, and physiological characteristics have not been systematically investigated. Here is reported the EBF rate, anatomical structure of shoot apical meristem and physiological characteristics of different seedlings at different storage temperatures (0, 3, 5, -3 and -5°C) and durations (14 to 125 d). The vernalization duration of seedlings was predicated from 57 to 85 d with temperatures ranging from 0 to 5oC. The EBF can be effectively inhibited by freezing storage. The anatomical structure of shoot apical meristem, levels of primary metabolites (soluble sugar, starch, amino acid and protein) and endogenous hormones (GA3, IAA and ABA), etc., exhibited a dynamical change at different storage temperatures. These findings will provide useful information for predicting the vernalization of seedlings and inhibiting the EBF in the large-scale commercial cultivation.